Końska mięta (Mentha arvensis), kobyli szczaw (Rumex obtusifolius) i krowi mlecz (Taraxacum officinale) - Olga Kielak (Ksiegarnia Akademicka Publishing, 2021)
Field Mint [Polish: “Horse Mint”] (Mentha arvensis), Curly Dock [Polish: “Mare Dock”] (Rumex obtusifolius) and Dandelion [Polish: “Cow Dandelion”] (Taraxacum officinale). On the Names of Farm Animals in Folk Phytonyms